2017
DOI: 10.1103/physreve.96.062902
|View full text |Cite
|
Sign up to set email alerts
|

Response of jammed packings to thermal fluctuations

Abstract: We focus on the response of mechanically stable (MS) packings of frictionless, bidisperse disks to thermal fluctuations, with the aim of quantifying how nonlinearities affect system properties at finite temperature. In contrast, numerous prior studies characterized the structural and mechanical properties of MS packings of frictionless spherical particles at zero temperature. Packings of disks with purely repulsive contact interactions possess two main types of nonlinearities, one from the form of the interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Studies [16] have suggested that β originates from the near-contacts represented in the divergent first peak of the radial distribution function [17] near jamming onset. However, interparticle contacts both form and break as the system is compressed above jamming onset [8]. Second, our recent studies [18] have shown that the shear modulus of individual jammed packings typically decreases with increasing p along geometrical families [19] that maintain the same contact network.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Studies [16] have suggested that β originates from the near-contacts represented in the divergent first peak of the radial distribution function [17] near jamming onset. However, interparticle contacts both form and break as the system is compressed above jamming onset [8]. Second, our recent studies [18] have shown that the shear modulus of individual jammed packings typically decreases with increasing p along geometrical families [19] that maintain the same contact network.…”
mentioning
confidence: 90%
“…When systems are below jamming onset φ < φ J , they possess too few interparticle contacts to constrain all degrees of freedom in the system, N c < N iso c [7], and they display fluid-like properties with zero static shear modulus. In systems composed of N spherical particles with purely repulsive interactions, no static friction, and periodic boundary conditions, N iso c = dN − d + 1 [8], where d is the spatial dimension, N = N − N r , and N r is the number of rattler particles that do not belong to the force-bearing contact network [9]. A number of groups have carried out computational studies to understand the structural and mechanical properties of jammed particulate solids with φ > φ J [10][11][12][13][14].…”
mentioning
confidence: 99%
“…The minimal number of contacts required for stability is the isostatic number, which is exactly reached at the jamming transition. In the vicinity of the transition, the solid is marginally stable 2,25 : a small perturbation can remove a few contacts and destabilize the entire solid 26,27 . This geometrical feature gives rise to low-frequency collective excitations that are extremely different from phonons 21,28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations of stress correlations support such unification. In simulations both of granular materials [7,8] and deeply supercooled liquids [9][10][11], the spatial shear-stress correlator has quadrapolar anisotropy and a power-law decay ∝ 1/r d in d dimensions. Similar observations have been made for strain correlations in experiment, both for colloids [12,13] and granular materials [14].…”
mentioning
confidence: 99%